Sustaining software teletrade in Bangalore: fostering market agility through economic competence - Millar, Jane (2000)
For firms in Bangalore, sustaining a presence in the international market for software involves combating cost-based competition as well as identifying and exploiting opportunities for market growth. This paper argues that successful firms are agile, capable of leveraging economic competence in the service of market dynamism. The paper develops and applies a profiling technique, based on `footprint analysis', to empirical data on active and leading software suppliers. It provides a typology of agile firms in Bangalore, identifies the sources of their economic competence and traces implications for government policies to sustain sectoral growth. - Reproduced
Keywords: Computer software